1979
DOI: 10.1104/pp.63.4.765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daylength on Phenol Metabolism in the Leaves of Salvia occidentalis

Abstract: A method of phenol determination in plant leaves has been developed which is based on the in situ oxidation of these compounds in an atmosphere containing ammonia, followed by difference spectrophotometry. The The daylength affects phenol metabolism in the leaves of plants (4,7,(11)(12)(13)15). Attempts have been made to relate this to photoperiodic phenomena, e.g. flower induction (11,13,15). Such a study is hampered by a number of problems. The fully grown plant carries leaves of different age and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…The harvest time also had an effect on its content. Engelsma [ 48 ] showed that in the light period the content of phenol (mainly chlorogenic and isochlorogenic acid) increases proportionally to the length of this period, which is also confirmed by our research.…”
Section: Discussionsupporting
confidence: 90%
“…The harvest time also had an effect on its content. Engelsma [ 48 ] showed that in the light period the content of phenol (mainly chlorogenic and isochlorogenic acid) increases proportionally to the length of this period, which is also confirmed by our research.…”
Section: Discussionsupporting
confidence: 90%
“…하지만 Zhang 등(2020)의 연구에 따 르면 광주기가 길어질수록 chlorophyll a, chlorophyll b, total chlorophyll의 함량이 감소하며 MDA의 축적이 증가한다고 보고되었는데 이는 본 실험과 유사할 것으로 예상된다. 페놀 은 식물의 항산화 물질 중 하나로 세포질 경계면에서 합성 하여 액포로 운반하는 과정을 거치는데 야간에는 이동이 멈추면서 분해되지만 주간에는 이동하여 함량이 증대된다(Engelsma, 1978;Engelsma, 1979; Kim 등, 2022). 광의 영 향으로 작물의 생합성 축적이 좌우되는데 광주기가 긴 것이 짧은 것보다 ROS 생성을 더 크게 유도하면서 페놀 화합물이 증가된다고 한다(de Andrade 등, 2021).…”
unclassified